The Use of e-Commerce in SMEs Sustainability of Asian Countries: The Literature Review - Nurrahma, Aisyah Asri; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (Jurnal Bisnis Mahasiswa, 2024)
This study aims to evaluate trends in publication and examine how SMEs use e-commerce for their sustainability in Asian countries. The systematic literature review (SLR) method was used to identify the phenomenon. After setting the inclusion and exclusion criteria, it was found that 26 articles will be analyzed using VOSviewer. The results show that 73 keywords are linked to each other, and they are categorized into three according to the mapping in VOSviewer. The themes we explored include the e-commerce adoption in SMEs that is beneficial for SMEs in Asia countries. E-commerce can become their competitive strategy, as well as reduce financial costs. Along with that, e-commerce can reach a broad audience for the product because it is easy to access. The next theme is the sustainability of SMEs through e-commerce and digitalization, which is found to have significantly impacted during and after the COVID-19 pandemic because of the shifting habit of online shopping. The last theme is SME digitalization, which uses not only e-commerce but also social media to do many things, such as communicating with the seller, offering the products, and even allowing consumers to order the product. Hence, it becomes an advantage for SMEs to adopt digitalization, especially using e-commerce and social media.